(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background:Multiple drugs resistance has increased due to the random use of available antimicrobial drugs in treatment of infectious diseases. Objective:To investigate probable antibacterial effects of fenugreek essential oil extract against Pseudomonas aeruginosa Methods:Twenty eight isolates of P. aeruginosa were collected from skin infected patients in Al- Yarmook teaching hospital in Baghdad. Antimicrobial susceptibility tests of 14 antibiotics were performed using Vitek2 compact system. The antibacterial activity of essential oil was evaluated using agar well diffusion method with minor modifications. The broth micro dilution method was used to determine minimum inhibitory concentration. Then animal experiment was performed in five groups of mice (n=7, for each) as following: control, induction, treated with fenugreek alone, treated with Gentamycin alone, treated with combination of fenugreek and Gentamycin. Then histopathological examination was done after seven days of the treatment. Results:P. aeruginosa isolates are highly resistance to trimethoprime/ sulfamethaxazole, while sensitive to amikacin. Minimum inhibitory concentration of fenugreek essential oil for highly resistance P. aeruginosa isolates (n=10) as followed: 6 isolates with minimum inhibitory concentration = 1.2gm/100µl, and 4 isolates with MIC= 0.6gm/100µl. Minimum inhibitory concentration of gentamycin was equal to>=16. Conclusion: Fenugreek essential oil has higher antibacterial effect alone and in combination with gentamycin than gentamycin alone. Keywords:Antibacterial activity, Fenugreek, Pseudomonas aeruginosa.